IMPULSIVE LOW-FREQUENCY SEISMOMAGNETIC SIGNALS IN GEOMAGNETIC VARIATIONS AS AN EARTHQUAKE PREDICTION TOOL - Naumov A.P. (My University, 1999)
This paper reports measurements of geomagnetic variations at a geodynamic test site in Crimea using fast optically pumped Sx-magnetometers in the summer seasons of 1981-1983. It shows possibilities for short-term earthquake prediction in the area of a reference magnetometer. Impulsive anomalies were identified in the variations (signals with amplitudes of 30-50 nT) which reflected some crustal processes preceding small earthquakes. The signals were recorded with magnetometers operated simultaneously at some distance from one another. This permitted an accurate determination of the source of the anomaly.